Educational Status of Sumi Women in Zunheboto District, Nagaland: Changing Dimensions - Kiba, Y. Inaholi (International Journal of Humanities and Education Development (IJHED), 2021)
This paper focuses on the educational status of Sumi women. It discusses the factors influencing education of Sumi women and also identifies the hindrances in the path of their education. Some of the key findings show that there is parental/family and societal support for women education. Women also feel that education elevates their status in society and leads to their empowerment both socially and economically. However, women are not involved in the decision making process concerning matters related to their villages and town thereby reflecting the patriarchal nature of the society which has never recognised women as primary decision makers. In addition, lack of economic resources contributes towards neglect of women education especially in rural areas